Investigation of the validity and reliability of the Turkish version of the Functional Assessment of Cancer Therapy-Cognitive Function in cancer patients - Atasavun-Uysal, Songül; Yıldız-Kabak, Vesile; Karakaş, Yusuf; Karabulut, Erdem; Erdan-Kocamaz, Deniz; Keser, İlke; Özdemir, Kadirhan; Düger, Tülin (Cambridge University Press, 2022)
Objective The Functional Assessment of Cancer Therapy-Cognitive Function (FACT-Cog) is a questionnaire that is used to evaluate the quality of life and cognitive functions according to individual self-reports. The aim of this study was to investigate the validity and reliability of the Turkish version of the FACT-Cog. Methods Cancer patients who were treated with chemo or radiotherapy and had a score of 24/30 and more in Mini-Mental State Examination (MMSE) were included in this study. Cognitive functions assessed with the FACT-Cog and the European Organization of Research and Treatment of Cancer Quality of Life Core Questionnaire Core 30: Cognitive Function subscale (EORTC QLQ-CF). Results One hundred and forty cancer patients [female = 87 (62.1%), male = 53 (37.9%)] were included. The mean age of the participants was 47.93 ± 11.90 years. The Cronbach's α of the FACT-Cog scale was 0.82. Test-retest intraclass correlation coefficient values of the FACT-Cog questionnaire were varied from 0.855 to 0.954. There were found low correlations between the total score of the FACT-Cog and the MMSE (r = 0.26, p = 0.002), and moderate correlations between the EORTC QLQ-CF subscale and the FACT-Cog (r =-0.43; p < 0.001). Significance of results It showed the validity and reliability of the Turkish version of the FACT-Cog questionnaire for cancer patients. It may be beneficial to use this questionnaire for the effects of cancer treatment. © 2021 The Author(s). Published by Cambridge University Press.
Keywords: cancer treatment; cognitive function; functional assessment; quality of life